OPTIMASI PENINGKATAN KUALITAS AIR SUMUR GALI MENJADI BAHAN BAKU AIR MINUM DENGAN MENGGUNAKAN KOMBINASI ZEOLIT DAN KAPUR TOHOR - Rusdiana Rusdiana; Danang Biyatmoko; Gusti Chairuddin; Azidi Irawan (EnviroScienteae, 2015)
Source of drinking water used of household in Banjarbaru is 50,97% water well protected/unprotected. The results Anisyah (2011) reported that the water quality of wells dug in Banjarbaru less fit for use as a water quality standard. This research aimed to analyze the effect of the combination of calcium oxide and zeolite and get the best combination to improve water quality dug into the raw material of drinking water in accordance Permenkes No.492/MENKES/PER/IV/2010. Dug well water as much as 10 l was added 1 g calcium oxide, in stir. Then passed through a zeolite column with 50 cm height with discharge 1 liter / minute, output collected and analyzed 2 liters (another treatment with the same procedure). Percentage reduction showed combination of the best Z1K2, which can reduce iron parameters 0,228 mg/l, manganese 0,136 mg/l, and 5 NTU turbidity, and then combination Z2K2 able to improve water quality dug well on parameter 51,50 TCU colors, smell and taste 2,55 (a bit smelly and tasteless), and pH of 7,95, and combination Z2K1 can reduce amount of E. coli 14,33 per 100 ml sample.